Development Trends of Nuclear Fusion Energy Technology and Its Industrial Chain - Jieru AN; Jiaxu ZUO; Xuyang HUANG; Wei SONG (南方能源建设)
[Objective] The paper aims to focus on the field of nuclear fusion energy, and in-depth study of related technologies and the development trends of industry chains. By reviewing the industrial development history, analyzing the current situation, and predicting future trends, the paper comprehensively examines the development trends of energy technology and industry chains. [Method] Based on multiple authoritative industry surveys, data analysis was conducted to organize the development history and current status of the nuclear fusion industry, analyze the trends in technological innovation and the distribution of technology fields, discover the intrinsic connections between technology, policy, and capital, predict the future direction of the industry, and reveal the development trends of the industry through data analysis. [Result] The study indicates that private enterprises have gradually become an important force in the nuclear fusion industry. Investors' confidence in the potential of nuclear fusion energy has been continuously strengthening. Policies issued by governments around the world have greatly promoted the vigorous development of the nuclear fusion industry. American companies have the broadest involvement in various technological fields of nuclear fusion, with a proportion of involved fields 1.7 times that of the second-ranked United Kingdom, and significantly higher than other countries. Almost all nuclear fusion companies have targeted power generation as their main market. In the derivative fields, industrial heat accounts for 28.6% of the derivative market choices in the entire survey, becoming the mainstream choice for most companies. There is a mutually reinforcing supportive relationship between technology, policy, and capital. [Conclusion] Looking at the development patterns of the nuclear fusion industry in recent years, technological innovation will continue to advance, capital will continue to expand, and policies around the world will remain optimistic.